Blaming the victim, all over again: Waddell and Aylward's biopsychosocial (BPS) model of disability. (February 2017) - Shakespeare, Tom; Watson, Nicholas; Alghaib, Ola Abu
The biopsychosocial model (BPS) of mental distress, originally conceived by American psychiatrist George Engel in the 1970s and commonly used in psychiatry and psychology, has been adapted by Gordon Waddell and Mansel Aylward to form the theoretical basis for current UK government thinking on disability. Most importantly, the Waddell and Aylward version of the BPS has played a key role as the government has sought to reform spending on out-of-work disability benefits. This article critiques Waddell and Aylward's model, examining its origins, its claims and the evidence it employs. We argue that its potential for genuine interdisciplinary cooperation and the holistic and humanistic benefits for disabled people as envisaged by Engel are not now, if they ever have been, fully realised. Any potential benefit it may have offered has been eclipsed by its role in Coalition/Conservative government social welfare policies that have blamed the victim and justified restriction of entitlements.